Critical organ dose evaluation during interventional stroke imaging: Implications for radiation safety - Ozgur, E.; Kayaokay, D. Tuncman; Ozgur, D. S.; Tunay, A.; Gunay, O.; Kesmezacar, F. F.; Demir, M.; ALMisned, G.; Tekin, H. O. (ELSEVIER SCI LTD, 2026)
Introduction: Neurointerventional stroke imaging involves prolonged fluoroscopy and multiple angiographic acquisitions, potentially delivering meaningful radiation doses to radiosensitive head and neck organs. This study quantified organ-specific absorbed doses under clinically realistic conditions. Methods: Organ doses were measured using calibrated MTS-100 LiF:Mg,Ti thermoluminescent dosimeters (TLD-100) placed in an Alderson Rando anthropomorphic phantom. Simulated stroke imaging was performed on a Siemens Artis Zee C-arm system using routine clinical parameters. TLDs were calibrated under RQR-9 beam quality at an accredited SSDL and read with a Harshaw 4500 reader. Results: The highest absorbed doses occurred in the left parotid gland and C1-C2 vertebral level. Bilateral thyroid doses averaged similar to 4.6 mGy, and eye lens doses ranged from 5.6 to 11.5 mGy. Dose distribution showed marked spatial variability, reflecting projection geometry and scatter contributions. Conclusion: Although measured single-session doses were below deterministic thresholds, cumulative exposure during repeated or prolonged interventions may become clinically significant. Implications for practice: The findings support the need for strict collimation, optimized projection angles, pulsed fluoroscopy, and continuous dose monitoring to minimize patient and staff exposure while maintaining diagnostic image quality. (c) 2026 The College of Radiographers. Published by Elsevier Ltd. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Radiation safety; Stroke imaging; ALARA; Clinical dosimetry; Radiology, Nuclear Medicine & Medical Imaging